The new product development process for commercial financial services - Edgett, Scott J.; McMaster University, Michael G. DeGroote School of Business, Innovation Research Centre (My University, 1996)
To achieve their goals, executives are increasingly reexamining their organizations' approach to development and launch of new products to determine if the process can be redesigned for faster reaction time, better utilization of limited resources and improved success rates. This article examines the new product development process within the setting of corporate/commercial financial services. Its conclusions provide executives with some broad principles for their own new product processes to help them in their quest for competitive advantage through winning new products.
14 leaves : ; Includes bibliographical references (leaves 13-14) ; "July, 1996".
Keywords: Business; Technology and Innovation; Business; Financial services industry New products > Management